Academic Self-Confidence and Peer Attachment: A Correlational Study of Islamic Junior High School Students - Sagita, Dony Darma (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study investigates the correlation between peer attachment and academic self-confidence among students in Islamic junior high schools (Madrasah Tsanawiyah). Employing a quantitative correlational approach, the study involved 77 early adolescent students selected randomly. Data were collected using two standardized instruments: the Peer Attachment Inventory (α= 0.95) and the Academic Self-Confidence Scale (α= 0.93). Before hypothesis testing, the normality assumption was verified using the Kolmogorov-Smirnov test, and linearity was assessed through the Test of Linearity in ANOVA, with both test met the significance criterion (p>0.05). The Pearson Product-Moment correlation analysis revealed a strong and statistically significant positive relationship between peer attachment and academic self-confidence (r=0.798, p<0.001). The results underscore the crucial roles of emotional closeness, trust, and communication among peers in shaping students’ academic resilience. Future studies are recommended to adopt experimental or longitudinal designs to examine the causal pathways and effectiveness of peer-based interventions in enhancing student well-being and performance.